The Correlation between Syntactic Knowledge and Reading Comprehension - Novita Pratiwi (Pascasarjana UM, 2019)
Abstract: This study aimed to find out the precise degree of relationship between syntactic knowledge (represented by grammar scores) and reading comprehension within EPT context. The data collected were in form of examinees’ individual scores of EPT taken from two language institutes. The data representing 160 examinees were divided into two sets of scores: grammar and reading. Utilizing statistical analysis software, the researcher analyzed the data using Pearson’s correlation coefficient. The result shows that syntactic knowledge and reading comprehension have strong positive correlation. It indicates that examinees’ grammar scores might predict their reading scores within EPT. Key Words: syntactic knowledge, reading comprehensionAbstrak: Penelitian ini bertujuan untuk mengetahui nilai pasti dari hubungan antara pengetahuan sin-taktis (diwakili oleh nilai tata bahasa) dengan pemahaman membaca dalam konteks EPT. Data yang ter-kumpul berbentuk nilai individu peserta EPT yang diperoleh dari dua lembaga bahasa. Data yang me-wakili 160 peserta dibagi menjadi dua: nilai tata bahasa membaca. Dengan memanfaatkan aplikasi anali-sis statistik, peneliti menganalisis data menggunakan koefisien korelasi Pearson. Hasilnya menunjukkan bahwa pengetahuan sintaksis dan pemahaman membaca memiliki korelasi positif yang kuat. Hal tersebut mengindikasikan bahwa nilai tata bahasa peserta mungkin dapat memprediksi nilai membaca mereka dalam EPT. Kata kunci: pengetahuan sintaksis, pemahaman membaca